2017
DOI: 10.1167/iovs.17-22312
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Intraocular Pressure Induces Amyloid-β Deposition and Tauopathy in the Lateral Geniculate Nucleus in a Monkey Model of Glaucoma

Abstract: For the first time to our knowledge, these data collectively establish the existence of hallmark AD-like pathologies in the glaucomatous LGN. Our results may provide new targets for developing research therapies that will enhance neuroprotection in glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 54 publications
(61 reference statements)
0
43
0
1
Order By: Relevance
“…However, visual impairments have also been described in AD patients as reflected by the reduction of visual acuity, contrast sensitivity, color vision, visual field and pupillary function (Uhlmann et al, 1991 ; Hutton et al, 1993 ; Gómez-Tortosa et al, 1996 ; Whittaker et al, 2002 ). Visual deficits may involve neuronal cell degeneration in the brain (Yan et al, 2017 ) and in the retina. Indeed, amyloid-β (Aβ) deposits and neurofibrillary tangles (NFTs) containing hyperphosphorylated Tau are classical histopathological features of AD that could also be observed in the retina of patients (Hart et al, 2016 ; Koronyo et al, 2017 ; Kusne et al, 2017 ; van Wijngaarden et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, visual impairments have also been described in AD patients as reflected by the reduction of visual acuity, contrast sensitivity, color vision, visual field and pupillary function (Uhlmann et al, 1991 ; Hutton et al, 1993 ; Gómez-Tortosa et al, 1996 ; Whittaker et al, 2002 ). Visual deficits may involve neuronal cell degeneration in the brain (Yan et al, 2017 ) and in the retina. Indeed, amyloid-β (Aβ) deposits and neurofibrillary tangles (NFTs) containing hyperphosphorylated Tau are classical histopathological features of AD that could also be observed in the retina of patients (Hart et al, 2016 ; Koronyo et al, 2017 ; Kusne et al, 2017 ; van Wijngaarden et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed an increased Aβ level in the optic nerve and RGC layer in glaucomatous animal models 21 , 22 , and tauopathy was also detected in the glaucomatous retina 23 . A recent study observed these AD-like pathologies in the lateral geniculate nucleus and primary visual cortex in a chronic hypertensive glaucoma monkey model 24 . However, the results of epidemiological studies are still conflicting.…”
Section: Discussionmentioning
confidence: 92%
“…e ., the progressive loss of neuron structure or function, including AD and PD, is currently recognized as a major public health issue with the aging global population 15 , 16 . There is increasing evidence of neurodegenerative lesions found in AD are also observed in the optic nerve, lateral geniculate nucleus, and visual cortex in glaucoma patients, suggesting that OAG is a neurodegenerative disease of the eye 17 24 . Previous experimental and clinical studies have shown close associations between OAG and PD 25 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Aβ deposition 29,30,31 Complement activation 6 Neuroinflammation + microglial activation 6 Neuronal cell death 6 Neuroinflammation + microglial activation 6 Neuronal cell death 6 As mentioned before, elevated IOP is common feature and the greatest risk factor for glaucoma. However, a link between glaucoma and AD has been proposed 26 , and the presence of protein deposits characteristic of AD (Aβ and pTau) has been described in the retinas of glaucoma patients 6,27,28 . Moreover, in both diseases comparable Aβ and pTau profiles are observed in the compartments closest to the primary affected tissue.…”
Section: Alzheimer´s Disease Parkinson´s Disease Glaucomamentioning
confidence: 99%